Competitive electricity markets design, implementation, performance - Sioshansi, Fereidoon P. (Elsevier, 2008)
After two decades, policy makers and regulators agree that electricity market reform, liberalization and privatization remains partly art. Moreover, the international experience suggests that in nearly all cases, initial market reform leads to unintended consequences or introduces new risks, which must be addressed in subsequent "reform of the reforms." This volume describes the evolution of the market reform process including a number of challenging issues such as infrastructure investment, resource adequacy, capacity and demand participation, market power, distributed generation, renewable energy and global climate change. ± Sequel to Electricity Market Reform: An International Perspective in the same series published in 2006 ± Contributions from renowned scholars and practitioners on significant electricity market design and implementation issues ± Covers timely topics on the evolution of electricity market liberalization world-wide.
Keywords: Electric utilities -- Management.; Electric power -- Marketing.; Competition.; elektronické knihy; electronic books